PENINGKATKAN KEMAMPUAN ANALISIS KESALAHAN SOAL DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH SETTING KOOPERATIF THINK-PAIR-SHARE PESERTA DIDIK KELAS VIII-B SMP NEGERI 25 MALANG - CHUSNUL CHOTIMAH (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
Application of problem-based learning gives students the abilities to create knowledge by themselves, develop higher mathematics skills, and increase self-confidence, in result. One of mathematics instruction strategies in which it is oriented to constructivism is cooperative learning in Think-Pair-Share (TPS). In Think-phase, teacher gives the students a problem, and then the students solve the problem by using their own method and strategy. Teacher guides the students to confirm their answer and strategy through a discussion with their partner (Pair-phase). After that, teacher points toward a group of students and asks them to present their discussion result in front of the class (Share-phase). The result of this research shows that: (1) Students’ activities are in active criteria for 1st and 2nd cycle (increasing from 84,52% to be 88,84%), (2) Teacher’s activities are in good criteria for 1st and 2nd cycle (increasing from 89,42% to be 91,83%), (3) Classical completeness of learning is 80,49% in 1st cycle and it is increasing to be 85,37% in 2nd cycle, average test score is 82,44 in 1st cycle and it is increasing to be 82,49 in 2nd cycle. ABSTRAKPenerapan pembelajaran berbasis masalah menjadikan peserta didik dapat menyusun pengetahuan sendiri, menumbuhkembangkan keterampilan yang lebih tinggi dan meningkatkan kepercayaan diri. Salah satu strategi pembelajaran matematika yang berorientasi pada pandangan konstruktivis adalah belajar kooperatif Think-Pair-Share (TPS). Pada tahap think guru memberikan permasalahan kepada peserta didik, kemudian peserta didik menyelesaikan masalah dengan cara atau strategi mereka sendiri. Guru mengarahkan peserta didik untuk mengkonfirmasi masing-masing jawaban dan strategi pemecahan masalah dengan pasangannya (pair). Selanjutnya guru menunjuk salah satu kelompok untuk mempresentasikan hasil diskusi di depan kelas (share). Hasil penelitian menunjukkan bahwa: (1) Aktivitas peserta didik berada pada kriteria aktif untuk siklus I dan II (meningkat dari 84,52% menjadi 88,84%), (2) Aktivitas guru berada pada kriteria baik untuk siklus I dan II (meningkat dari 89,42% menjadi 91,83 %), (3) Ketuntasan belajar secara klasikal mencapai 80,49% pada siklus I meningkat menjadi 85,37% pada siklus II, nilai rata-rata hasil tes adalah 82,44 pada siklus I meningkat menjadi 82,49 pada siklus II.